Pentingnya Ilmu Jiwa Agama dalam Kehidupan (Tinjauan: Teori dan Konsep Ilmu Jiwa) - Sudirman Sudirman (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2021)
Religion Soul Science is defined as a science that studies the symptoms of a normal, mature and civilized human soul. Psychology is now used generally for the study of human behavior and experience. Psychology of religion examines the influence of religion on attitudes and behavior of people or mechanisms that work within a person, because the way a person thinks, behaves, reacts and behaves cannot be separated from his beliefs, because beliefs are included in personal construction.